Breaking Barriers to Good Agricultural Practices - Rochelle, E.J.S.; Guruge, T.P.S.R. (University of Jaffna, 2025)
Amid increasing globalization and its implications for public health and trade, food safety has emerged as a critical concern. In Sri Lanka, agriculture remains a cornerstone of the national economy, necessitating adherence to internationally recognized standards, such as Good Agricultural Practices (GAP). Despite the introduction of GAP certification in 2007, adoption remains limited, particularly in the Northern Province. This study aims to identify and analyze key barriers to GAP certification and propose strategic interventions to enhance its adoption and effectiveness. Using a mixed-methods approach, data were collected from 35 purposively sampled stakeholders across nine categories, including five Agricultural Instructors, three Agribusiness development officers, three GAP Technical Assistants, seven GAP Certified farmers, nine Non-GAP Certified Farmers, two GAP Sales outlets, two GAP Training officers, two SME’s involved in the value chain, and 2 GAP Certifying officers. Tools included structured surveys, in-depth interviews, and FGDs, supported by secondary sources. Quantitative data were analyzed using descriptive statistics, correlation analysis, and Relative Importance Index (RII) rankings; qualitative inputs were analyzed thematically. Findings revealed low GAP awareness among non certified farmers and strong dissatisfaction with market incentives among certified farmers. A statistically significant correlation was observed between training exposure and awareness levels. Key barriers included insufficient market demand (RII = 0.88), knowledge gaps (RII = 0.81), certification costs (RII = 0.77), and infrastructure deficiencies (RII = 0.71). Retailers reported minimal consumer interest, with only 12–15% of shelf stock being GAP certified. Cluster analysis further grouped stakeholders based on attitudes and engagement, revealing critical disconnects between supply, policy, and market actors. To address these findings, the study proposes a multi-pronged strategy: enhancing training and awareness, establishing a centralized market intelligence system, incentivizing certifying officers, introducing premium-based pricing models, and strengthening certified product distribution. These reforms are vital to ensure food safety, raise agricultural profitability, and elevate Sri Lanka's position in global agri-trade.
Keywords: Agricultural policy; Farmer incentives; Food safety; Market barriers; Sustainable Agriculture